1973
DOI: 10.1063/1.1679704
|View full text |Cite
|
Sign up to set email alerts
|

Raman characterization studies of synthetic and natural MgAl2O4 crystals

Abstract: Articles you may be interested inMagnetic anisotropy and order structure of L10-FePt(001) single-crystal films grown epitaxially on (001) planes of MgO, SrTiO3, and MgAl2O4 substrates Magnetism and magnetotransport in symmetry matched spinels: Fe3O4/MgAl2O4

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

1991
1991
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 61 publications
(26 citation statements)
references
References 8 publications
1
25
0
Order By: Relevance
“…No modes were found at 225 and 727 cm-1 as previously on synthetic spinel, see Table 2 ( O'Horo et al 1973;Fraas et al 1973; see also Ishii et al 1982). Broad weak features present in the baseline of the spectra at 445, 525, 610, and 718 cm -1 were confirmed as being intrinsic to the crystal by examining the anti-Stokes spectrum and/or using the 457.9-nm laser line for excitation.…”
Section: Ramanmentioning
confidence: 81%
See 3 more Smart Citations
“…No modes were found at 225 and 727 cm-1 as previously on synthetic spinel, see Table 2 ( O'Horo et al 1973;Fraas et al 1973; see also Ishii et al 1982). Broad weak features present in the baseline of the spectra at 445, 525, 610, and 718 cm -1 were confirmed as being intrinsic to the crystal by examining the anti-Stokes spectrum and/or using the 457.9-nm laser line for excitation.…”
Section: Ramanmentioning
confidence: 81%
“…Fraas et al (1973) found these extra modes and a few additional broad peaks in their synthetic spinels. Fraas et al's synthetic spinels displayed a varying degree of disorder as shown by the broadening and loss of resolution of the fluorescence spectrum.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Doping effect of transition metals has also been well studied [10][11][12]. Phonon structure has been clarified by Raman spectroscopy [13] and electronic states of doped transition-metal are also understood through their electron spin resonance (ESR) spectrum [14,15].…”
Section: Introductionmentioning
confidence: 99%